PENGARUH KECERDASAN EMOSIONAL TERHADAP PENGGUNAAN MEDIA SOSIAL PADA PESERTA DIDIK - Rohyadi, Kadmyel; Wicaksono, Luhur; Fergina, Ana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aimed to determine the influence of emotional intelligenceon the use of social media in class IX students at SMP Negeri 22Pontianak. This study used a quantitative approach with descriptivemethod and the form of research used is survey research. Thepopulation in this study was 141 students in class IX, with a totalsample 42 respondents. The collection technique used, namelyindirect communication techniques with questionnaire data collectiontools. Based on the results of the study, it was found that the level ofemotional intelligence possessed by class IX students was 81% in the"High" category. Meanwhile, the level of use of social media in classIX students was 79% in the "Medium" category. Based on this, in theresults of data analysis, there is a significant influence of emotionalintelligence on the use of social media in class IX students, namely27% and there were as many as 73% who were influenced by othervariables not examined.